Design and Development of a Body Fat Percentage Measurement System Using the Bioelectrical Impedance Analysis (BIA) Foot-to-Foot Method - Ruciyanti, Febrian; Sumanto, Budi (Universitas Muhammadiyah Surakarta, 2024)
A person's nutritional status is ideally determined based on a body composition assessment, which differentiates the fat mass and fat-free mass in a human body. Fat and fat-free mass can be calculated using a non-invasive method called bioelectrical impedance analysis (BIA). In this research, a body fat measurement system was designed using the BIA foot-to-foot method, which is also equipped with the automatic body mass and height measurements system using a load cell sensor and a ToF VL53L1X sensor. The BIA method is designed to flow a 0.4mA current with a frequency of 50kHz into the body using four electrodes through the object’s feet. Other parameters required in this system, such as age and gender, will be entered using the keypad. The computing and data processing process uses an Arduino Nano microcontroller and is displayed on the LCD. The system that has been designed is then compared with a similar measuring instrument, Mi Scale Body Composition 2. The results obtained in this study are: the average error value for measuring body weight is 0.43kg; the average error for measuring height is 1.13cm; the average error in measuring BMI is 0.32 kg/m2; and the average error in measuring body fat percentage is 3.25%.